POLA PENGASUHAN BERSAMA DALAM PUTUSAN 0334/PDT.G/2019/PA.GDT TENTANG PENYELESAIAN SENGKETA HAK ASUH ANAK DI PENGADILAN AGAMA GEDONG TATAAN - Hi Salasa, Masriah; Muhdar, Muhammad Halman (Mabahits : Jurnal Hukum Keluarga Islam, 2025)
This study aims to examine and further analyze the legal reasons that underlie the decision to establish shared parenting as a solution for resolving child custody disputes that were applied by the Gedong Tataan Religious Court judge as stated in his decision number 0334/Pdt.G/2019/ PA.Gdt. Research Results That the context of the parkara which is the object of study in this thesis research stems from the divorce lawsuit and child custody dispute (Haḍānah) filed by "S N bint I" as the Plaintiff against "E R Bin I H" as the Defendant. From the result of their marriage, they were blessed with one child (named RA, aged 4 years and 6 months). In legal considerations the Judge in deciding cases of child custody disputes is based on reasons for the best interests of the child, and in order to prevent a prolonged conflict between the Plaintiff and the Defendant as parents, besides that based on the facts the Judge believes that the Plaintiff and Defendant have the psychological skills to carry out their parenting duties. , and have good ethics and morals, which are expected to be emulated by the children they care for. In addition, the norms that underlie the judge's legal considerations include provisions in the law related to child protection, exercising discretion over the interpretation of the provisions of Article 105 of the KHI as well as the provisions of Islamic law. The legal considerations used by the judge in deciding the a quo case emphasized that child care is not only related to the realization of maintaining offspring (al-nasl), preserving the soul (al-nafs), and reason (al-aql) at the al-dar-riat level, but at the same time also religion (al-din) at the level of al-tahsiniyat